One-step eco-friendly synthesized silver-graphene oxide/poly(vinyl alcohol) antibacterial nanocomposites. (September 2019) - Cobos, Mónica; De-La-Pinta, Iker; Quindós, Guillermo; Fernández, M. Jesús; Fernández, M. Dolores
Abstract: Due to the increasing occurrence and spread of antibiotic resistance pathogenic microorganisms, the development of antimicrobial materials has emerged as a strategy to control the bacterial activity and transmission. In this study, poly(vinyl alcohol)/silver nanoparticles-graphene oxide (PVA/AgNPs-GO) nanocomposites were synthesized by a one-step process withl -ascorbic acid as environmentally friendly reductant agent of a mixture of AgNO3, GO and PVA aqueous solutions. PVA/GO nanocomposites were also prepared for comparison. The structure, morphology, thermal, mechanical, water resistance and antibacterial properties of the samples were investigated as a function of GO and silver precursor contents. GO sheets decorated with spherical AgNPs were uniformly dispersed in the polymer matrix. The size range of most AgNPs was below 10 nm. Nanocomposites exhibited higher glass transition and crystallization temperatures. Thermal stability, mechanical and water resistance properties of PVA enhanced when GO was incorporated, and it was more remarkable in the presence of AgNPs-GO. PVA/AgNPs-GO nanocomposites showed antibacterial activity against Gram negative bacteria Escherichia coli and against Gram positive bacteria Staphylococcus aureus, being its efficiency dependent on exposure time and AgNPs precursor concentration. In contrast, PVA/GO films showed no activity against both bacteria over the GO loading range investigated. PVA/AgNPs-GO nanocomposites may be potential wound dressings. Graphical abstract: Image 1